2018
DOI: 10.1111/1462-2920.14060
|View full text |Cite
|
Sign up to set email alerts
|

The virome of the arbuscular mycorrhizal fungus Gigaspora margarita reveals the first report of DNA fragments corresponding to replicating non‐retroviral RNA viruses in fungi

Abstract: Arbuscular Mycorrhizal Fungi (AMF) are key components of the plant microbiota. AMF genetic complexity is increased by the presence of endobacteria, which live inside many species. A further component of such complexity is the virome associated to AMF, whose knowledge is still very limited. Here, by exploiting transcriptomic data we describe the virome of Gigaspora margarita. A BLAST search for viral RNA-dependent RNA polymerases sequences allowed the identification of four mitoviruses, one Ourmia-like narnavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 63 publications
(89 reference statements)
0
41
0
Order By: Relevance
“…Their wide diversity warrants the establishment of a family taxon called Mitoviridae, separated from the family Narnaviridae. The newly established family would comprise a number of subfamilies and genera, including the very distantly related mitovirus species characterized from the arbuscular mycorrhyzal fungus Gigaspora margarita, which are included in a clade basal to existing characterized mitoviruses (37). As already observed by other authors (17), plant mitoviruses are nested in a specific fungal mitovirus clade, raising questions about the evolutionary trajectory of plant mitoviruses, which has been discussed at length elsewhere (17).…”
Section: Discussionmentioning
confidence: 76%
“…Their wide diversity warrants the establishment of a family taxon called Mitoviridae, separated from the family Narnaviridae. The newly established family would comprise a number of subfamilies and genera, including the very distantly related mitovirus species characterized from the arbuscular mycorrhyzal fungus Gigaspora margarita, which are included in a clade basal to existing characterized mitoviruses (37). As already observed by other authors (17), plant mitoviruses are nested in a specific fungal mitovirus clade, raising questions about the evolutionary trajectory of plant mitoviruses, which has been discussed at length elsewhere (17).…”
Section: Discussionmentioning
confidence: 76%
“…Despite classic mitoviruses typically show genome sizes of about 2.3–2.7 kb, we identified two viral contigs which are phylogenetically related to mitoviruses but which showed genome of 3067 (Alternaria alternata mitovirus 1) and 3520 (Epicoccum nigrum mitovirus 1) nucleotides (both encoding only for the RdRp). Mitoviruses of similar genomic size were also previously reported for the arbuscular mycorrhizal fungus Gigaspora margarita (Turina et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…For example, the endobacterium Candidatus Glomeribacter gigasporarum was shown to increase sporulation, ATP production, reactive oxygen detoxification and responsiveness to the plant signal strigolactones of the fungal host, G. margarita (Salvioli et al ., ). In addition, viruses can thrive inside AMF, yet our knowledge on the AMF virome is limited to few AMF species (Ikeda et al ., ; Kitahara et al ., ; Turina et al ., ). In particular, Ikeda et al .…”
Section: Perspectivesmentioning
confidence: 97%
“…Tansley review New Phytologist fungal host, G. margarita . In addition, viruses can thrive inside AMF, yet our knowledge on the AMF virome is limited to few AMF species (Ikeda et al, 2012;Kitahara et al, 2014;Turina et al, 2018). In particular, Ikeda et al (2012) demonstrated that a virus-free fungal strain produced more spores and promoted plant growth more efficiently than the viruscontaining strain.…”
Section: Reviewmentioning
confidence: 99%